2001
DOI: 10.1071/wr00075
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of two indices of red fox (Vulpes vulpes) abundance in an arid environment

Abstract: The suitability of spotlight counts to index red fox abundance was assessed in an arid environment through a comparison with a scat deposition index (active attractant). In most cases there was a high degree of correlation between the two indices, suggesting that the spotlight counts were accurately documenting fluctuations in population size. However, the precision of the spotlight index was often low (c.v. = 0.07–0.46), suggesting that the technique may not allow the statistical detection of small changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 19 publications
2
31
0
Order By: Relevance
“…Faeces (scats) do not appear to be used in social communication in this species ( Macdonald 1980), such that underlying patterns of scat deposition are unlikely to vary with density and social disruption, but that scat numbers will vary with density per se. Faecal counts have been shown to be a reliable index of abundance in fox species in terms of comparisons between spatial locations (Cavallini 1994) and to reflect changes in fox numbers between seasons (Sharp et al 2001). In addition, estimates of absolute abundance derived from faecal counts have been shown to correlate well with estimates derived from other methods in the UK (see Webbon et al 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Faeces (scats) do not appear to be used in social communication in this species ( Macdonald 1980), such that underlying patterns of scat deposition are unlikely to vary with density and social disruption, but that scat numbers will vary with density per se. Faecal counts have been shown to be a reliable index of abundance in fox species in terms of comparisons between spatial locations (Cavallini 1994) and to reflect changes in fox numbers between seasons (Sharp et al 2001). In addition, estimates of absolute abundance derived from faecal counts have been shown to correlate well with estimates derived from other methods in the UK (see Webbon et al 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Under the socalled 'sign surveys' (Clevenger 1993) include many different survey methodologies, from snow tracking (Pullianen 1981;Zielinski and Kucera 1995) to scat counting along paths (Cavallini 1994;Virgó s et al 2000;Virgó s 2001;Webbon et al 2004), den enumeration (Cresswell et al 1989;Wilson et al 1997) or spoor counts (Smallwood and Fitzhugh 1995;Staender 1998). Most of these methods have not been tested in relation to true population density, but recent research has indicated a close fit between sign abundance and density for several carnivore species (Staender 1998;Sharp et al 2001;Tuyttens et al 2001;Sadlier et al 2004;Webbon et al 2004), despite early criticisms about accuracy (Kruuk et al 1986;Norton 1990). As a consequence, several researchers recommended the use of sign surveys as the main element in national monitoring programmes or large-scale studies (Macdonald et al 1998;Toms et al 1999;Baker et al 2002;Sadlier et al 2004;Webbon et al 2004; but see Birks et al 2004).…”
Section: Introductionmentioning
confidence: 96%
“…However, because carnivores are usually scarce, elusive and nocturnal, they are very difficult to count by traditional methods such as transects based on direct observation (e.g. spotlight or line-transects, Heydon et al 2000;Sharp et al 2001) or capture-recapture estimates based on trapping records (Tuyttens et al 1999). These problems are especially relevant when the study needs to consider large spatial scales (Zielinski and Kucera 1995;Zielinski and Stauffer 1996;Webbon et al 2004), where high economic costs and field efforts are necessary to achieve a reliable estimate (Smallwood and Fitzhugh 1995;Sadlier et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Ralls andEberhardt (1997), Edward's et al (2000), Heydon et al (2000) and Sharp et al (2001). Studies generally comment on the derived density precision (Edwards et al, 2000;Sharp et al, 2001), but few have focused on precision itself (Stahl and Migot, 1990).…”
Section: Introduction and Literaturementioning
confidence: 96%
“…Transects have been used previously to provide an accurate assessment of mammal populations for monitoring population changes for conservation and management purposes (Barnes and Tapper, 1985;Stahl and Migot, 1990;Heydon et al, 2000;Caley and Morley, 2002). However, certain aspects of spotlighting and its validity have been questioned (Mahon et al, 1998;Sharp et al, 2001). One major concern is low precision (Edwards et al, 2000), a key determinant of the accuracy of estimated density and another is the species detection bias (Jones and Coman, 1982;Mahon et al, 1998).…”
Section: Introduction and Literaturementioning
confidence: 98%